Integration definition methods to support product design for assistive technology - Okumura, Maria Lucia Miyake; Canciglieri Junior, Osiris; de Souza, Teófilo Miguel [UNESP]; Young, Robert I. M. (Trans Tech Publications, 2014)
Integrated Product Development Process (IPDP) oriented for Assistive Technology (AT) usually engages multidisciplinary areas for design development. The involvement of professionals from different areas contributes to strengthening the IPDP phases, but a major barrier is the correct interpretation and understanding of the information shared by them, which allows the addressing of the product's requirements and the feeding of the design structure. This paper aims to outline the first steps of the IPDP oriented for TA using the Integrated Definition Methods (IDEF) tool applied to a device design to assist in the training of athletes with visual disabilities. This step of the process focused on Object-Oriented Design Method (IDEF4) and Ontology Capture Method (IDEF5) from IDEF family. The result shows that through the use of the IDEF method oriented for the design of an AT product, the information sharing and the design global aspect to all team members was favored, promoting better communication. © (2014) Trans Tech Publications, Switzerland.
Keywords: Assistive technology; IDEF; Integrated product development; Paralympic sports athletes with visual disability